Genome‐wide microRNA and messenger RNA profiling in rodent liver development implicates mir302b and mir20a in repressing transforming growth factor‐beta signaling1. Issue 6 (26th April 2013) - Wei, Wei; Hou, Juan; Alder, Olivia; Ye, Xin; Lee, Sam; Cullum, Rebecca; Chu, Andy; Zhao, Yongjun; Warner, Stephanie M.; Knight, Darryl A.; Yang, Decheng; Jones, Steven J.M.; et al.
Abstract MicroRNAs (miRNAs) are recently discovered small RNA molecules that regulate developmental processes, such as proliferation, differentiation, and apoptosis; however, the identity of miRNAs and their functions during liver development are largely unknown. Here we investigated the miRNA and gene expression profiles for embryonic day (E)8.5 endoderm, E14.5 Dlk1+ liver cells (hepatoblasts), and adult liver by employing Illumina sequencing. We found that miRNAs were abundantly expressed at all three stages. Using K‐means clustering analysis, 13 miRNA clusters with distinct temporal expression patterns were identified. mir302b, an endoderm‐enriched miRNA, was identified as an miRNA whose predicted targets are expressed highly in E14.5 hepatoblasts but low in the endoderm. We validated the expression of mir302b in the endoderm by whole‐mount in situ hybridization. Interestingly, mir20a, the most highly expressed miRNA in the endoderm library, was also predicted to regulate some of the same targets as mir302b. We found that through targeting Tgfbr2, mir302b and mir20a are able to regulate transforming growth factor beta (TGFβ) signal transduction. Moreover, mir302b can repress liver markers in an embryonic stem cell differentiation model. Collectively, we uncovered dynamic patterns of individual miRNAs during liver development, as well as miRNA networks that could be essential for the specification and differentiation of liver progenitors. (HEPATOLOGY 2013)